2017
DOI: 10.1371/journal.pone.0184160
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in elderly: Clinical characteristics, treatments and outcomes compared with younger adults

Abstract: The number of elderly patients diagnosed with hepatocellular carcinoma (HCC) is expected to increase. The present study aims to evaluate the role of age on treatments and outcome of HCC patients. 1530 patients firstly diagnosed with HCC were retrospectively included and classified as older (≥65 years, n = 318, 21%) and younger patients (<65 years, n = 1212, 79%). The two groups were compared with clinical characteristics, tumor burden, Barcelona Clinics Liver Cancer (BCLC) stage, treatments and long-term progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
4
31
1
Order By: Relevance
“…This rate was high. Previous studies have reported that the number of elderly patients with HCC is increasing [20] and that elderly patients have higher rates of HCV or NBNC than nonelderly patients [14,15,20,21], which is consistent with our results. HCV infections generally occur in adulthood, in contrast to HBV infections, which are generally acquired through mother-child transmission [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This rate was high. Previous studies have reported that the number of elderly patients with HCC is increasing [20] and that elderly patients have higher rates of HCV or NBNC than nonelderly patients [14,15,20,21], which is consistent with our results. HCV infections generally occur in adulthood, in contrast to HBV infections, which are generally acquired through mother-child transmission [22].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, gastric [11], colorectal [12], and breast [13] cancers show poorer prognoses in young patients than in elderly patients. There have been some reports concerning HCC; however, the conclusions of these reports are controversial [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of tools for evaluating the operative indications have been developed, including the APACHE score and E‐PASS score, elderly patients are selected for surgery based on the same criteria as young patients in our centre. In general, elderly patients who undergo operations tend to have more comorbidities than young patients, such as hepatitis C viral (HCV) infection, respiratory disease and diabetes, and they also have a poor performance status . Regarding HCV infection, elderly patients have shown a poor response to interferon therapy due to severe side effects or insufficient compliance with drug intake.…”
Section: Discussionmentioning
confidence: 99%
“…More elderly patients receive non‐surgical therapies than young patients, even if their HCC is operable. Hui et al . showed that elderly patients (≥65 years of age) were less often effectively treated with surgery and loco‐regional therapies across different Barcelona Clinic Liver Cancer (BCLC) stages than younger patients.…”
Section: Discussionmentioning
confidence: 99%